KONSTRUKSI GAGASAN FEMINISME ISLAM KHALED M. ABOU EL-FADL: Relevansinya Dengan Posisi Perempuan Dalam Keluarga - Habuddin, Ihab (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2012)
Abou Fadl realizes that women are often in oppressed position. He then attempts to reconstruct Muslim’s understanding position of women inferiority and tries to promote women as creatures to and equal on the men. This indicates that his ideas are in the same position to that of Islamic feminism. This article attempts to discuss the construction of the Abou Fadl’s idea on feminism, this will concentrate on two important things: first, the epistemology of thought, deals with how Abou Fadl understands the text, in which he uses hermeneutics to understanding Islamic law. The second, the ideas of feminism, deals with main ideas of Abou Fadl’s feminism. This will focus on his criticism to the various fatwa about gender, the use of misogynist hadis, and his concept about the nature and nurture of women. In addition, this article also discusses the typology of the idea of Abou Fadl’s feminism and the position of women in Islamic family.[Abou Fadl menyadari bahwa perempuan sering kali berada pada posisi yang tertindas. Ia kemudian berupaya merekonstruksi pemahaman umat Islam yang merendahkan perempuan dan memposisikan perempuan sebagai makhuk bebas dan setara dengan laki-laki. Artikel ini mencoba membahas konstruksi gagasan feminisme Abou Fadl, yaitu: pertama, epistemologi pemikiran, berkaitan dengan bagaimana Abou Fadl memahami teks, di mana ia menggunakan hermeneutika negosiatif sebagai cara memahami hukum Islam. Kedua, hasil pemikiran, berkaitan dengan ide-ide pokok feminisme Abou Fadl, yakni tentang kritiknya terhadap berbagai fatwa bias gender, penggunaan hadis-hadis misoginis, dan konsepnya tentang sifat dan dasar-dasar perempuan. Selain itu, artikel ini juga membahas tipologi gagasan feminisme Abou Fadl dan posisi perempuan dalam keluarga Islam.]